2014
DOI: 10.1016/j.wem.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Wound Care in the Wilderness: Is There Evidence for Honey?

Abstract: Honey is one of the most ancient remedies for wound care. Current research has shown promising results for its use in wound care. This review is intended to inform readers of the physiological properties of honey and the evidence that exists to support its clinical use. When compared with evidence for current wound treatment, honey has proven to be a safe, effective, and sometimes superior treatment for various wounds. There are currently US Food and Drug Administration–approved medical-grade honey products av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 71 publications
0
24
0
5
Order By: Relevance
“…Studies have also shown that MGO is effective against S. aureus that has become resistant to methicillin and oxacillin [9]. Kilty et al (2011) reported that MGO was also effective against P. aeruginosa, S. aureus including MRSA biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have also shown that MGO is effective against S. aureus that has become resistant to methicillin and oxacillin [9]. Kilty et al (2011) reported that MGO was also effective against P. aeruginosa, S. aureus including MRSA biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria MGO is mainly synthesized from the glycolytic intermediate, dihydroxyacetone However excessive amounts of MGO such as found in manuka honey kill bacteria, and MGO has been found to have a bacteriostatic and bactericidal effects across a broad spectrum of wound bacteria [9]. Growth inhibition of bacteria occurs when MGO levels in the growth media reaches 0.3 mM and viability decreases at levels above 0.6 mM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Honey is a natural food produced in almost every region of the world, with recognized uses -mainly as a sweetener (Chaven 2014) and an alternative medicine for the treatment of various diseases (Saxena et al 2014;Stewart et al 2014). The composition of a specific honey depends on the floral richness in the surroundings of the hive, but it mainly contains sugars, water, amino acids, organic acids, phenolic compounds, enzymes, pigments, waxes, volatile substances, traces of pollen, other secondary metabolites, etc.…”
Section: Introductionmentioning
confidence: 99%